Explanation:
To give you a hand for this question, I will show you how to work out one of the equations
One equation is
![y - 1 = (-5)/(4) (x-2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/9ycwlnwbrp6wpi4oldpgapyneuvk2a82c1.png)
We know that when x = -2, y = 6
So we can substitute in -2 and see if we get 6
![y - 1 = (-5)/(4) (-2-2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/2v7ymvhlj1a81revbh5mbws5cflqu7b6l9.png)
![y - 1 = (-5)/(4) * (-4)](https://img.qammunity.org/2022/formulas/mathematics/high-school/traub7c23482l1guyt5beptlmp5md8l11e.png)
![y - 1 = 5](https://img.qammunity.org/2022/formulas/mathematics/high-school/2jjnub22gxfrzk7zkmakj6r8jv8nkpgkol.png)
![y = 5 + 1](https://img.qammunity.org/2022/formulas/mathematics/high-school/ebo3yqigljk4fagrhr44d5s22fy809hr8h.png)
![y=6](https://img.qammunity.org/2022/formulas/mathematics/college/ffrluzwx83os6i6ndkgjpia880gpjlek6h.png)
So this equation is true! Now try the same for the other equations :)